The Consequences of the Coronavirus Disease 2019 Pandemic on Smoking Behavior: Evidence from the English Longitudinal Study of Ageing. Issue 2 (13th April 2022) - Gaggero, Alessio
Abstract: Introduction: Smoking is a risk factor for the progression of COVID-19, with smokers having higher odds of COVID-19 progression than never-smokers. This study presents novel findings on the effect of the COVID-19 pandemic on smoking behavior in older adults. Methods: Panel data were obtained from the English Longitudinal Study of Ageing ( N = 60160, 12% smokers, 55% women, 62% married, mean age = 67 years, 23% employed). Fixed-effect regression models were used to estimate the extent to which the COVID-19 pandemic affected smoking behavior. A separate model was estimated for men, women, employed, and retired. Results: The findings suggest a significant and positive effect of the COVID-19 pandemic on smoking behavior (β = 0.024; P < .001). The estimated effects were stronger for men and for the sample of individuals reporting being employed. Conclusions: In this study, I provide robust evidence of the effect of the COVID-19 pandemic on smoking behavior using the English Longitudinal Study of Ageing. This large and representative dataset is uniquely suited for the analysis. I find evidence that the proportion of smokers has increased significantly as a result of the COVID-19 pandemic. Implications: In the United Kingdom, the proportion of smokers increased significantly as a consequence of the COVID-19 pandemic. These findings suggest that smoking behavior may have been used as a mechanism to cope with depression, stress, and anxiety due to the COVID-19 outbreak. To the extent to which smoking behavior has been used as a coping mechanism to deal with job-related issues, targeted policy action to provide financial stability to those in worse economic situations may have beneficial effects on smoking behavior.